Identification of Bacteria Isolated from Sea Urchin (Diadema setosum) Gonads Inhibiting Pseudomonas fluorescens and Staphylococcus aureus Growth - Andini Maurent Dwiyanti; Helen Joan Lawalata; Iriani Setyawati; Anita Constanci Christine Tengker; Nonny Manampiring (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Sea urchins are organisms that have antibacterial, antitumor, and anticancer abilities. The gonads can be used as a food source because they store 28 kinds of amino acids, vitamin B complex. This research aims to determine the type of bacteria from the gonads of sea urchins (Diadema setosum) which have inhibitory power against the growth of Pseudomonas fluorescens and Staphylococcus aureus bacteria. This research used an exploratory method which was analyzed descriptively, using stages in which sea urchin samples were taken and antibacterial tests against Pseudomonas fluorescens and Staphylococcus aureus from sea urchin gonads using the spread method. The media used for the process of isolating bacteria from the gonads of the sea urchin Diadema setosum is Nutrient Agar (NA) media. Isolate colonies that grew after incubation for 24 hours were separated based on differences in colony morphology. Morphological characterization of bacterial cells begins with gram staining. The diameter of the inhibition zone in the test bacteria shows different shapes. The research obtained 8 bacterial isolates, namely isolates B1-B8 which were gram-negative. The eight bacterial isolates have the potential as antibacterials against the test bacteria P. fluorescens and S. aureus. Isolates B1, B2, B3, B7 are similar to the genus Proteus, while isolates B4, B5, B6, and B8 are similar to the genus Citrobacter. The diameter of the largest inhibition zone in the P.fluorescens test bacteria, namely isolate B1, was 9.03 mm. Meanwhile, the smallest diameter for isolate B7 was 6.97 mm. In the S.aureus test bacteria, the largest diameter in isolate B1 was 11.09 mm. Meanwhile, the smallest diameter for isolate B4 was 8.57 mm.